Chronic systemic exposure to IL6 leads to deregulation of glycolysis and fat accumulation in the zebrafish liver - Singh, Manoj K.; Jayarajan, Rijith; Varshney, Swati; Upadrasta, Sindhuri; Singh, Archana; Yadav, Rajni; Scaria, Vinod; Sengupta, Shantanu; Shanmugam, Dhanasekaran; Shalimar; Sivasubbu, Sridhar; Gandotra, Sheetal; et al. (Biochimica ET Biophysica Acta-Molecular and Cell Biology of Lipids, 2021)
Inflammation is a constant in Non-Alcoholic Fatty Liver Disease (NAFLD), although their relationship is unclear. In a transgenic zebrafish system with chronic systemic overexpression of human IL6 (IL6-OE) we show that inflammation can cause intra-hepatic accumulation of triglycerides. Transcriptomics and proteomics analysis of the IL6-OE liver revealed a deregulation of glycolysis/gluconeogenesis pathway, especially a striking down regulation of the glycolytic enzyme aldolase b. Metabolomics analysis by mass spectrometry showed accumulation of hexose monophosphates and their derivatives, which can act as precursors for triglyceride synthesis. Our results suggest that IL6-driven repression of glycolysis/gluconeogenesis, specifically aldolase b, may be a novel mechanism for fatty liver. This mechanism may be relevant for NAFLD in lean individuals, an emerging class of NAFLD prevalent more in Asian Indian populations.
Keywords: Aldolase b; DHAP; Inflammation; Interleukin 6; Lean NAFLD; Non-alcoholic fatty liver